Use of mesh phasing to locate faulty planet gears. (1st February 2019) - Peng, Dikang; Smith, Wade A.; Randall, Robert B.; Peng, Zhongxiao
Highlights: We explain the root cause of observed asymmetry in planet gear fault signals. Sequential mesh phasing of the planet gears is responsible. Indicator proposed based on timing of fault symptoms relative to gearmesh phase. Indicator can locate a faulty planet gear if a phase reference is available. The first time mesh phasing relationships have been used for diagnostics. Abstract: It is a challenge to determine by vibration analysis which planet gear carries a fault due to the complex layout of planetary gearboxes. In this study, we explain for the first time the possibility of using mesh phasing for distinguishing between faults on different planet gears. It has been found that, due to mesh phasing relationships, the vibration signals recorded on a planetary gearbox test rig exhibit different characteristics depending on the position of the faulty gear. These tests used localised seeded spalls giving impulsive signals, and it was found that due to the sequential mesh phasing arrangement, the timing of the fault-related impulse responses, as measured relative to the phase of the gearmesh component, depends on which planet is faulty. These timing differences can also give rise to different levels of asymmetry in the signal. This paper proposes a phase-based approach to differentiate and locate the faulty planet gear position using vibration response signals, and an indicator is developed for this purpose. With the assistance of absolute phase information, acquired through a tachometer on the planet carrier, the phase indicator is able to locate the position of the faulty gear. The approach has been applied to recorded experimental signals and it is found that the method can diagnose the position of the faulty gear effectively.